A Novel Gene Delivery Vector of Agonistic Anti-Radioprotective 105 Expressed on Cell Membranes Shows Adjuvant Effect for DNA Immunization Against Influenza - Yamazaki, Tatsuya; Biswas, Mrityunjoy; Kosugi, Kouyu; Nagashima, Maria; Inui, Masanori; Tomono, Susumu; Takagi, Hidekazu; Ichimonji, Isao; Nagaoka, Fumiaki; Ainai, Akira; Hasegawa, Hideki; Chiba, Joe; et al. (Frontiers in Immunology, 2020)
Radioprotective 105 (RP105) (also termed CD180) is an orphan and unconventional Toll-like receptor (TLR) that lacks an intracellular signaling domain. The agonistic anti-RP105 monoclonal antibody (mAb) can cross-link RP105 on B cells, resulting in the proliferation and activation of B cells. Anti-RP105 mAb also has a potent adjuvant effect, providing higher levels of antigen-specific antibodies compared to alum. However, adjuvanticity is required for the covalent link between anti-RP105 mAb and the antigen. This is a possible obstacle to immunization due to the link between anti-RP105 mAb and some antigens, especially multi-transmembrane proteins. We have previously succeeded in inducing rapid and potent recombinant mAbs in mice using antibody gene-based delivery. To simplify the covalent link between anti-RP105 mAb and antigens, we generated genetic constructs of recombinant anti-RP105 mAb (αRP105) bound to the transmembrane domain of the IgG-B cell receptor (TM) (αRP105-TM), which could enable the anti-RP105 mAb to link the antigen via the cell membrane. We confirmed the expression of αRP105-TM and the antigen hemagglutinin, which is a membrane protein of the influenza virus, on the same cell. We also found that αRP105-TM could activate splenic B cells, including both mature and immature cells, depending on the cell surface RP105 in vitro. To evaluate the adjuvanticity of αRP105-TM, we conducted DNA immunization in mice with the plasmids encoding αRP105-TM and hemagglutinin, followed by challenge with an infection of a lethal dose of an influenza virus. We then obtained partially but significantly hemagglutinin-specific antibodies and observed protective effects against a lethal dose of influenza virus infection. The current αRP105-TM might provide adjuvanticity for a vaccine via a simple preparation of the expression plasmids encoding αRP105-TM and of that encoding the target antigen.